Penerapan prinsip good corporate governance dan corporate social responsibility di Pondok Pesantren - Hendrayuda Suwarno (Department of Accounting Universitas PGRI Yogyakarta, 2024)
The research aims to determine the application of the principles of Good Corporate Governance and Corporate Social Responsibility in Islamic Boarding Schools. The research was conducted at the Modern Muhammadiyah Boarding School (MBS) Islamic Boarding School in Yogyakarta in 2021/2022. This study employs a qualitative approach that begins with data and leads to conclusions. This study also translates research findings from the field into the researchers' language, using these data to explain the existing conditions. In this study, the data were analyzed by determining the lowest and highest score ranges: multiplying the number of respondents (n) by the lowest weight (1) and the highest (5), yielding a lowest GCG principles implementation score of 20 and a highest of 100. Then determine the range of scores for each criterion (20(5-1))/5=16. The study results indicated that the overall application of GCG principles was Good, with a total score of 419.3; thus, the assessment score (419.3/5) = 83.86.